PERKEMBANGAN MORFOLOGI KOTA GORONTALO DARI MASA TRADISIONAL HINGGA KOLONIAL - Irfanuddin Wahid Marzuki (BRIN, 2018)
Abstract Gorontalo is the biggest city and the forerunner of the present Gorontalo Province. Gorontalo has been existing since traditional era, Islamic kingdoms, colonial, and up to the present. During the traditional and kingdom era, Gorontalo was the small kingdom included in Ternate area. In fact, it witnessed the changes of power during colonial era when it was excluded from Manado regency. It remained the same even until independence time, Gorontalo became the area of North Sulawesi Province until in the year 2000 became its own province. The purpose of this research is to reveal the morphological development of the city respectivelly from traditional to colonial era in addition to find out the background factor of the morphological development. This research used urban archaeology whose main studies are urban components, including urban planning as well as city life as the inseperable component. This research underwent the following steps, collecting data, analysis and interpreting data resulted in a conclusion. The data collections includes primary data and secondary one (archive, text, maps, and other literacy sources). The result suggested that during traditional era the morphological city of Gorontalo was simple, and the settlement was spreading in small groups and doesn not have a regular urban planning component. The starting point as a city with regular spatial components began during the reign of Sultan Botutihe. Subsequent developments in the colonial period of the city center moved to the south referring to the rule of law of indies.